Accumulating bright excitons on the hybridized local and charge transfer excited state for organic semiconductor lasers. Issue 27 (4th July 2022) - Chen, Rui; Zhou, Wu; Gong, Yanjun; Zhou, Zeyang; Wang, Hong; Dai, Chenghu; Zhao, Yong Sheng; Che, Yanke; Zhang, Chuang; Yao, Jiannian
Abstract : The hybridization of local and charge transfer excited states is proven to accumulate bright excitons for both optically pumped lasing and electroluminescence at high current density. Abstract : Simultaneously realizing high exciton density and high emission efficiency in light emitting devices is generally challenging because of the competition between exciton accumulation and its radiative recombination. Here, we demonstrate that the hybridized local and charge-transfer (HLCT) excited state in a twisted donor–acceptor molecule can be used to accumulate highly luminescent excitons, leading to both efficient optically pumped lasing and improved electrically injected luminescence. The twisted molecular structure brings the hybridization characteristics of both locally excited (LE) and charge-transfer (CT) states, where the LE component ensures the remarkable quantum yield (>60%) of radiative decay and the CT contribution prolongs the exciton lifetime to a few nanoseconds. By incorporating the HLCT molecule into the polymer semiconductor, optically pumped lasing is achieved from their microspheres, and the threshold is significantly reduced compared with that of the LE molecule. Magneto-photoluminescence measurement reveals that the introduction of CT characteristics is beneficial to the efficient accumulation of bright excitons at high pump intensity. Moreover, the HLCT molecule doped polymer is used as an active layer in organic light emitting diodes, in which the electroluminescence intensity is enhanced by 2 orders of magnitude compared with its LE counterpart especially at high electric current density. The magneto-electroluminescence of the HLCT material decreases at >50 mT fields and is opposite to its magneto-photoluminescence, which reveals the distinct contribution of the CT component in exciton accumulation under optical pump and electrical injection. These findings provide new insights into the design and synthesis of optical gain molecules towards high-performance organic lasers upon optical excitation as well as those under electrical injection conditions.